2017
DOI: 10.1177/1555412017740497
|View full text |Cite
|
Sign up to set email alerts
|

Game Theory for Computer Games Design

Abstract: Designing and developing computer games can be a complex activity that may involve professionals from a variety of disciplines. In this article, we examine the use of game theory for supporting the design of gameplay within the different sections of a computer game and demonstrate its application in practice via adapted high-level decision trees for modeling the flow in gameplay and payoff matrices for modeling skill or challenge levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…At the same time, we should fully consider the personal physical condition and improve the inheritance effect of the game decision model. Some scholars on 65 cases of researchers found that the game decision model can carry out factor analysis of sports shuttlecock inheritance, the analysis results are ideal and consistent with the results of this study [ 23 ]. Some scholars have proposed that young people aged 20~30 should analyze the inheritance of sports shuttlecock to verify the influence of game decision model on the inheritance of sports shuttlecock [ 24 ].…”
Section: Discussionsupporting
confidence: 86%
“…At the same time, we should fully consider the personal physical condition and improve the inheritance effect of the game decision model. Some scholars on 65 cases of researchers found that the game decision model can carry out factor analysis of sports shuttlecock inheritance, the analysis results are ideal and consistent with the results of this study [ 23 ]. Some scholars have proposed that young people aged 20~30 should analyze the inheritance of sports shuttlecock to verify the influence of game decision model on the inheritance of sports shuttlecock [ 24 ].…”
Section: Discussionsupporting
confidence: 86%
“…In general, theory is useful to explain certain phenomenon which in this context is learning through digital games. However, some of the studies on educational digital games support the usefulness of the theory underpinning and guiding the overall look of the game design (Ahmad et al, 2015;Clark et al, 2015;Elsattar, 2017;Ishak et al, 2021;Kiili, 2005;Mat Zin & Wong, 2013;Pereira de Aguiar et al, 2018;Plass et al, 2015;Rooney, 2012;Sung et al, 2017;Taylor et al, 2017;Wu et al, 2012;Zaibon & Shiratuddin, 2010). Wu et al (2012) identified that there are four types of major learning theory used in educational digital games, namely behaviourism, cognitivism, humanism, and constructivism.…”
Section: The Need For Theorymentioning
confidence: 99%
“…Meanwhile, McKinsey's 2022 report emphasized the importance of virtual branded fashion and in-game collaborations to engage fashion consumers in the coming five years (Balchandani et al, 2022). On the other hand, Taylor et al (2019) highlighted game-theory as a formal approach to conceptualize decision-making processes in gaming environments. In this emerging research topic, identifying how gaming influences fashion branding strategies and brand reach is an urgent research gap.…”
Section: Discussionmentioning
confidence: 99%